Unusual presentation of advanced prostate cancer in a black population of South-Western Nigeria - Salako, Abdulkadir (Pan Afr Med J, 2019)
There are growing concerns on the varying pattern of advanced prostate cancer (PCa) presentation across the world. We report some of the unusual presentations of PCa at the Obafemi Awolowo University Teaching Hospitals Complex (OAUTHC), Ile-Ife, South-Western Nigeria. A review of all patients with histologically confirmed PCa who had unusual presentations between January 2014 and December 2015 was done. Unusual presentation was defined as an atypical feature in the absence of lower urinary tract symptoms (LUTS), with the diagnosis of PCa only suspected after abnormal digital rectal examination (DRE) and/or elevated prostate specific antigen (PSA) assay. Thirteen patients had an unusual presentation in OAUTHC during the study period. Five (38.5%) had left supraclavicular swellings while four (30.8%) had haematochyzia and tenesmus. Other unusual presentations include large bowel obstruction requiring emergency colostomy (2;15.4%) and a scalp mass (1;7.7%). All patients had appropriate treatment for stage of PCa and are being followed up in the out-patient clinic. The change in presentations of PCa may suggest the need for DRE and serum PSA assay among all middle-aged and elderly men presenting at health facilities. Large scale studies on PCa across different population groups may also help at identifying related clinical, demographic and epidemiological factors as well as possible validation of some of these unusual presentations.